1997
DOI: 10.1038/sj.gt.3300513
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-mediated transfection with peptides containing arginine-glycine-aspartic acid domains

Abstract: Two synthetic peptides comprising an RGD moiety for intecase of the COS-7 and A375M cell lines. With the ECV304 grin binding and a polylysine moiety for DNA binding were cell line, optimum transfection occurred in the absence of tested for transfection efficiency under a variety of different chloroquine. Transfection efficiency of the peptides was conditions. Binding of target cells to the peptide was shown greatest at peptide:DNA ratios of 4:1 (w/w), which were to be strongly dependent on cyclisation of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 8 publications
1
51
0
Order By: Relevance
“…54,55 More closely related work with a vector containing a RGD peptide coupled to an oligolysine showed epithelial cell lines to be transfected; 41 in this system, a minimum number of 5000 ligands per complex, an about 6:1 N/P ratio as well as extra endosomolytic agents such as chloroquine, 42,56 polyethylenimine or inactivated adenovirus 42 were required. In our system, epithelial and fibroblast cells were already efficiently transfected with unmodified PEI-DNA complexes having a strongly positive surface charge via the 'ionic' gene transfer mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 More closely related work with a vector containing a RGD peptide coupled to an oligolysine showed epithelial cell lines to be transfected; 41 in this system, a minimum number of 5000 ligands per complex, an about 6:1 N/P ratio as well as extra endosomolytic agents such as chloroquine, 42,56 polyethylenimine or inactivated adenovirus 42 were required. In our system, epithelial and fibroblast cells were already efficiently transfected with unmodified PEI-DNA complexes having a strongly positive surface charge via the 'ionic' gene transfer mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35] In addition, we have demonstrated that the presence of a liposome enhances substantially the level of gene expression of this construct. 1,32,36 It was, however, not clear whether this enhancement is entirely due to the targeting function of the oligo-peptide or if it may also be able to confer a nuclear targeting function by virtue of its strong positive charge.…”
Section: -1653mentioning
confidence: 99%
“…Therefore, the RGD peptide was rapidly synthesized in a cyclized form in order to mimic its natural environment within the protein. One of the first "cyclization" was performed by bridging two cysteine side chains placed at the two extremities of the peptide [140,141].…”
Section: Cyclizationmentioning
confidence: 99%